Native mixed microbe inoculants (M1H) optimize soil health to promote Cajanus cajan growth: the soil fungi are more sensitive than bacteria - Liu, Zexun; Luo, Chengcheng; Zheng, Kang; Sun, Yongtao; Ru, Jie; Ma, Yaner; Zhang, Xinru; Zhou, Yong; Zhuang, Jiayao (Frontiers in Microbiology, 2025)
Microbial inoculant is widely used in plant growth and crop production. However, the effect of native mixed microbial inoculants on soil microbiota and plant growth remain to be elucidated. Here, we used pot experiment for 5 months to determine the microbial inoculants treatments with growth-promoting effect on Cajanus cajan, such as M1P (Serratia marcescens) treatment and M1H treatment: the mixture of M1P and M45N (Paenibacillus polymyxa), and investigate the effect of these inoculants on the capacity of soil nutrients and rhizosphere microbiomes in promoting C. cajan growth. Further, the adaptability of these strains to environmental stress (temperature and pH) was determined by using stress-resistant growth experiment. The results showed that M1H treatment resulted in soil nutrients consumption and led to substantial alterations in the microbial community that were more effective in promoting C. cajan growth. The enhanced plant growth observed with M1H inoculation may be due to its impact on the soil micro-environment, particularly through increasing beneficial genera (e.g., Cunninghamella, Mortierella, Chryseolinea, and Bacillus) and decreasing potential genera (e.g., Zopfiella and Podospora). In addition, at the genus level (top 10), the effect of M1H inoculation on soil fungal community was higher than that of bacteria, which shows that the change of soil fungal community after M1H inoculation was more sensitive than that of bacteria. Spearman correlation analysis further revealed that the abundance of Cunninghamella, Mortierella, Chryseolinea, Zopfiella and Podospora were the key factors affecting C. cajan growth. Moreover, FUNGuild function prediction clearly indicated distinct differences in the fungal functions of CK, MIP and M1H treatment, in which a lower relative abundance of saprotroph fungi in M1H treatment compared to CK, these results may confirmed the possibility of decreasing the abundance of Zopfiella and Podospora under M1H treatment. Taken together, our findings highlight the role of M1H inoculant in promoting C. cajan growth and ameliorating soil health, and providing valuable insight of using native mixed microbial inoculants to cultivate C. cajan and optimize soil micro-environment.